61 The inconsistent choices of inotropic and vasopressors at the front door in patients with ischaemic cardiogenic shock and its impact on in-hospital mortality. (4th June 2021) - Tran, Patrick; Shabana, Amanda; Dholoo, Farzan; Banerjee, Prithwish
Abstract : Background: Despite no evidence of survival benefit, inotropes and vasopressors continue to be routinely used in the setting of acute myocardial infarction with cardiogenic shock (CS). ESC recommends noradrenaline as vasopressor and dobutamine as inotrope of choice. These are only class IIb recommendations with level B/C evidence. Yet on admission, these agents are initiated almost invariably by intensivists. We believe such prescriptions are inconsistent amongst intensivists and linked with adverse outcomes. After all, inattentive use increases the risk of infarct expansion and ventricular arrhythmias. We also hypothesize that some patients with initial CS stabilize after revascularization without needing vasoactive support and are associated with lower mortality rates. Method: In this single-centre retrospective analysis of 116 patients with ischaemic CS, we examined the type of vasoactive agents initiated on admission and their respective baseline characteristics and angiography data ( table 1 ). Four treatment groups were identified (vasopressors- noradrenaline and metaraminol; inotropes- adrenaline, dobutamine and dopamine; combination; no treatment), and analysed in relation to in-hospital mortality by adjusted multivariable logistic regression. We also performed a subgroup analysis of the same outcome for individual drugs and their combinations. Results: All vasoactive agents were decided by on-call intensivists. Overall, patients were aged 68±13 years, with average systolic BP (SBP) 71±16 mmHg. As expected, prescriptions of vasoactive agents were highly variable: vasopressors (16%), inotropes (15%), combination (34%) or no treatment (34%). Overall inpatient mortality was 43%. Patients on vasopressors (p=0.015), inotropes (p=0.029) or combination (p=0.002) were significantly more likely to die than those without treatment. Indeed, the latter group had a lower proportion of out-of-hospital arrests and marginally higher SBP. Compared to no treatment, adrenaline and metaraminol significantly increased the odds ratio of in-patient death by 3.82 (CI 1.49-9.79, p=0.005) and 2.9 (CI 1.23-6.97 p=0.016) respectively. In contrast, there was a trend of the noradrenaline group to be lower risk (OR 0.96) albeit non-significant. There were no differences with dobutamine or dopamine. A combination of adrenaline-dobutamine was associated with increased in-patient mortality (p=0.009) (table 2). Conclusion: This study confirms the inconsistent use of vasopressors and inotropes at the front door in patients with acute MI and CS. This needs to be more aligned to address the disparity between ESC guidance and intensivist practice. Metaraminol with its ease of use peripherally is associated with a 3-fold increase in inpatient mortality. This study also reminds us that not all ischaemic CS cases are sustained since with prompt revascularization, vasoactive agents and their associated adverse effects can be avoided or used for the shortest possible duration. Conflict of Interest: None